The Fundamental Concepts of Vladimir Bibikhin’s Metaphysics (sophia - strangeness - interest) - Pogrebnyak, Aleksandr (Stasis, 2015)
This article attempts to articulate and develop key concepts of Vladimir Bibikhin’s metaphysics, as presented in a series of important lecture courses. These concepts form the triad “sophia—strangeness—interest,” in some ways serving as a “translation” of M. Heidegger’s “world—finitude—solitude” (from the subtitle of his Fundamental Concepts of Metaphysics) into the hermeneutic language of the Russian 1990s. As is well known, Bibikhin translated the first chapters of this book, as well as a range of other important works by Heidegger. Despite their significant influence upon him, Bibikhin’s own metaphysical thought is truly original, since his goal is not the construction of a distinctive system but the reproduction here and now, in concrete historical circumstances, of an original philosophical gesture of seeing – indicating, in particular, his interest in the themes of energy, property, the woods, as well as his constant attention to the idiosyncrasy of Russian reality (beyond “westernizing” criticism and “slavophile” praise). In the concluding section of the article, I show how important the works of N. V. Gogol are for understanding Bibikhin’s thought, as he periodically refers to this author’s texts, either explicitly or implicitly.